Mass larval mortalities in giant freshwater prawn, Macrobrachium rosenbergii de Man, cultured in Malaysian modified static‘green water’ systems - Anderson, I. G.; Shariff, Mohamed; Nash, G. (Wiley Blackwell, 1990)
Repeated mass mortalities occurred in larval Macrobrachium rosenbergii de Man reared in modified static‘green water’ systems in two commercial hatcheries in Malaysia. Mean age of larval cultures at the time of mass mortalities was 164 days, or at larval stage 8 or 9. Gross signs, wet mount preparation pathology and/or histopathology revealed bacterial necrosis, midcycle larval disease-like and idiopathie muscle necrosis associated tissue changes, in some cases together with uncharacterised fungal infections. Strict attention to hatchery hygiene and the sanitary lot technique was effective in reducing the occurrence of mass larval mortalities.